2015
DOI: 10.4187/respcare.04212
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Transcutaneous Carbon Dioxide Monitoring—Effect on Clinical Management and Outcomes

Abstract: BACKGROUND: This work aimed to compare frequency of blood gas measurements per day of mechanical ventilation, occurrence of extreme blood gas CO 2 values, and clinical outcomes among ventilated neonates managed with and without transcutaneous carbon dioxide (P tcCO 2 ) monitors. This work also measures agreement between simultaneous P tcCO 2 and blood gas CO 2 measurements and ascertains factors that affect agreement. METHODS: This is a cohort study with retrospective analysis comparing 5,726 blood gas measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 16 publications
4
36
0
3
Order By: Relevance
“…Beck et al [28] in a systematic review on the use of NAVA in children reported the mean Edi values ranging between 8 and 20 mcV. In the present study, the values of Edi peak on NIV NAVA and CPAP are similar to as reported by different authors [21,24], and falls within the range described by Beck et al It shows reproducibility and may indicate optimal respiratory muscle unloading on NIV NAVA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Beck et al [28] in a systematic review on the use of NAVA in children reported the mean Edi values ranging between 8 and 20 mcV. In the present study, the values of Edi peak on NIV NAVA and CPAP are similar to as reported by different authors [21,24], and falls within the range described by Beck et al It shows reproducibility and may indicate optimal respiratory muscle unloading on NIV NAVA.…”
Section: Discussionsupporting
confidence: 90%
“…Edi waveform is an estimate of the patient's own neuronal drive and is independent of any leaks giving information about lung stretch, respiratory muscle loading, and other inputs [17]. The utility of Edi monitoring while on respiratory support can be compared to the utility of end-tidal CO2 or transcutaneous CO2 monitoring in the intensive unit [24]. Since the majority of premature infants needing NIV require feeding catheters for either feeding or gastric decompression, Edi catheter tracings can be considered as an additional bedside clinical tool to monitor the effectiveness of the noninvasive support.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous CO 2 monitoring is commonly used to reduce the frequency of arterial blood gas analysis in neonates due to the limitations of other methods to estimate PaCO 2 in this population, such as end-tidal CO 2 and capillary blood gas analysis 22. Yet we identified weak evidence for accuracy and precision with population limits of agreement that were far outside the clinically acceptable range.…”
Section: Discussionmentioning
confidence: 78%
“…The Cochrane Neonatal Review Groups concluded that there was no evidence to recommend or refute the use of tcPCO 2 monitoring to prevent neonatal morbidity and mortality . However, the use of tcPCO 2 monitoring decreased the frequency of blood gas samplings among ventilated neonates without affecting the duration of mechanical ventilation or clinical outcome . The Neonatal Research Network in Japan, has reported the progress in survival and neurodevelopmental outcome of the infants born at the “limit of viability” .…”
Section: Discussionmentioning
confidence: 99%
“…18 However, the use of tcPCO 2 monitoring decreased the frequency of blood gas samplings among ventilated neonates without affecting the duration of mechanical ventilation or clinical outcome. 19 The Neonatal Research Network in Japan, has reported the progress in survival and neurodevelopmental outcome of the infants born at the "limit of viability". 1,2 Transcutaneous blood gas monitoring was expected to be useful (30.4%) in future neonatal medical care in Japan.…”
Section: Discussionmentioning
confidence: 99%